Capital City Cruising: Surveillance, Pleasure, and Discursive Practices of Queer Communities in Ottawa - Kenyon, Miles (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2024)
This study investigates how men who have sex with men (MSM) discern, discuss, and defy issues of surveillance in the context of casual, public sex—also known as cruising—and how these exchanges constitute and inform subaltern counter-surveillance measures. Focusing on written exchanges by users of the queer hook-up website Squirt, I analyze how individuals share information about the safety and surveillance of cruising locations in the Greater Ottawa Area. This work concludes that surveillance and cruising is normalized, and that both police and ordinary citizens present safety risks. Because of this, great care is taken to act discreetly and not infringe on the safety of non-cruisers. Finally, environmental factors contribute greatly to both the construction and circumvention of surveillance infrastructure. The data additionally complicate surveillance realism (Dencik and Cable 2017), since cruisers accept the presence of surveillance but not the inevitable impact of it.